Temporal changes in symptomatic intracranial arterial disease: a longitudinal high-resolution vessel wall imaging study - Kang, Dong-Wan; Kim, Jonguk; Kim, Do Yeon; Baik, Sung Hyun; Jung, Cheolkyu; Menon, Bijoy K.; Song, Jae W.; Han, Moon-Ku; Bae, Hee-Joon; Kim, Beom Joon (Frontiers in Neurology, 2025)
IntroductionThe temporal dynamics of the vessel wall in intracranial arterial disease (ICAD) may differ depending on the etiology. We investigated temporal changes in narrowed intracranial arteries after ischemic stroke using serial high-resolution vessel wall imaging (HR-VWI).MethodsWe retrospectively recruited patients with ICAD-related ischemic stroke who underwent two or more HR-VWI scans. The lumen area (LA), total vessel area (TVA), and enhancing area (EA) of the narrowest part of the culprit lesion were manually segmented. Degree of stenosis was estimated as [1-LA/TVA] × 100(%), the enhancing proportion as EA/TVA × 100(%), and enhancement ratio as (T1GDlesion/T1GDref)/(T1lesion/T1ref). Linear mixed models were used to investigate temporal changes in these parameters and whether such changes differed by etiologies.ResultsOf a total of 208 patients, ICAD-related stroke was caused by atherosclerosis (69%), arterial dissection (24%), vasculitis (3%), moyamoya disease (1%), and other (2%). The median follow-up was 319 [IQR, 125–409] days. HR-VWI imaging parameters, namely, degree of stenosis, enhancing proportion, and enhancement ratio showed a trend to decrease over time. Patients with intracranial dissection as a cause of intracranial narrowing showed a faster reduction in degree of stenosis and enhancing proportion vs. when such narrowing was identified as due to atherosclerosis (β [95% CI], −0.59%[−0.80% −0.38%] and −0.81%[−1.23% −0.39%], respectively, both p < 0.01). The enhancement ratio did not change over time in dissection, while it decreased in atherosclerosis (−0.01 [−0.02 0], p = 0.04).ConclusionIntracranial vessel narrowing in patients with ischemic stroke changes over time with different stroke etiologies having their own unique temporal patterns.